1986
DOI: 10.2105/ajph.76.11.1293
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of low carbohydrate and low fat/high fiber diets for weight loss.

Abstract: Among 135 overweight subjects, we conducted a three-month randomized controlled trial of two sets of dietary advice, each providing approximately 1,000 calories per day but differing in fiber, carbohydrate, and fat content. Information on weight and eating habits, as well as measures of lipoprotein and glucose metabolism were obtained at entry and one and three months later. We found that dieters given low carbohydrate/low fiber dietary advice tended to lose more weight than those given a higher carbohydrate/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 16 publications
0
36
2
Order By: Relevance
“…The literature on rates of weight loss with different diet components in conventional dietetic practice is rather small. The results of Baron et al (1986) were unexpected in showing greater weight loss on a low CHO diet. Other studies have failed to show differences on higher versus lower CHO and dietary ®bre diets (Alford et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The literature on rates of weight loss with different diet components in conventional dietetic practice is rather small. The results of Baron et al (1986) were unexpected in showing greater weight loss on a low CHO diet. Other studies have failed to show differences on higher versus lower CHO and dietary ®bre diets (Alford et al, 1990).…”
Section: Discussionmentioning
confidence: 91%
“…The view that starchy foods such as bread and potatoes promote obesity remains widespread in the 1990s despite an almost universal shift in scienti®c opinion, to favour the use of high CHO (high ®bre) diets for slimming. Baron et al (1986), however, described greater weight loss with a low CHO diet in a free living sample. Bortz et al (1967Bortz et al ( , 1968 employed very low calorie diets (800 kcal/d) in a captive metabolic ward condition and found no difference between the rates of weight loss with diets containing high or low energy from CHO, leading to the classic assertion`a calorie is a calorie'.…”
Section: Introductionmentioning
confidence: 86%
“…However, the important question remains whether a specific macronutrient composition of the diet can facilitate reduction of energy intake under realistic ad libitum conditions. Table 1 shows the characteristics and results of randomized trials that compared diets that had the same explicit energy intake target, but differed in carbohydrate content (Baron et al, 1986;Pascale et al, 1995;Lean et al, 1997;McManus et al, 2001). Although dietary advice included a specific target for energy intake, the long duration of these studies and 'free living' conditions precluded strict control of the energy intake of the participants.…”
Section: Total Carbohydrate Intakementioning
confidence: 99%
“…In one study quoted in NICE guideline 43, a subgroup analysis found that a low-carbohydrate/low-fibre diet tended to be more successful for weight loss among people in a lower social class (classes III-IV) than a higher-carbohydrate/higher-fibre diet. 25 Clearly, more targeted research may be helpful, especially given recent evidence suggesting effectiveness of low carbohydrate diets. [25][26][27] Social interventions aimed at tackling obesity also offer an alternative interesting approach.…”
Section: Possible Ways Forward and Future Researchmentioning
confidence: 99%
“…25 Clearly, more targeted research may be helpful, especially given recent evidence suggesting effectiveness of low carbohydrate diets. [25][26][27] Social interventions aimed at tackling obesity also offer an alternative interesting approach. 28 Evidence from interventions in 'real life' primary care are also much needed and approaches such as 'Counterweight' in the UK are being watched with interest.…”
Section: Possible Ways Forward and Future Researchmentioning
confidence: 99%